Pengaruh Pemberian Pupuk Organik Cair (Daun Lamtoro + Batang Pisang) terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) - Warisa, Neni Loka; Syamsuwirman; Bustari Badal (Fakultas Pertanian, Universitas Ekasakti, 2022)
Research on the effect of giving POC (lamtoro leaves + banana stem) on the growth and yield of cucumber (Cucumis sativus L.) has been carried out in Korong Gadang Village, Kuranji District, Padang, February - May 2021. The aim of the study was to obtain the best POC concentration for growth and cucumber yields. The design used was a randomized block design with 5 treatments and 5 groups so that there were 25 experimental units, the experimental unit was a plot with a size of 200 x 210 cm, a spacing of 70 x 50 cm so that in each experimental unit there were 15 plants, 5 of which were used as sample plants for observation. . The treatments given were various concentrations of POC, namely: A = No POC 0 ml/l water, B = POC 50 ml/l water, C = POC 100 ml/l water, D = POC 150 ml/l water, E = POC 200 ml/l water. The data obtained were analyzed statistically with the F test, if the F-count > F-table then continued with the DNMRT test at a 5% significance level. The results showed that the administration of POC showed significantly different effects on the number of segments, the number of fruit planted, the number for plots, the weight of the fruit in the plantation, and the weight of the fruit in the plots; significantly different to the number of female flowers and harvest age; and not significantly different for plant length, fruit diameter and fruit length. The treatment that showed the best effect was 100 ml/l water. Based on the results of the study, it is recommended to use a POC dose of 100 ml/l of water for cucumber plants.